Fabrication of g-C3N4and a promising charcoal property towards enhanced chromium(VI) reduction and wastewater treatment under visible light - Suphatchaya Lamkhao (2018)
© 2017 Elsevier Ltd The visible light driven photoactivity of g-C3N4can be enhanced using charcoal as a supporter. Charcoal/g-C3N4composite materials were prepared by the simultaneous thermal condensation of melamine and charcoal. The effect of different atmospheres (O2, air, and argon) on the reaction was investigated. The effect of different weight ratios of charcoal to melamine (1:1 and 1:4 wt%) was also investigated. The physical properties of the charcoal/g-C3N4materials were analyzed using XRD, SEM, TEM, XPS, BET and FTIR techniques. It was found that an oxidation reaction of charcoal and g-C3N4during preparation greatly affected the photoactivity. A composite of charcoal:melamine (1:4 wt%) prepared under an air atmosphere provided good photooxidation of methylene blue; whereas a composite of charcoal:melamine (1:4 wt%) prepared under an oxygen atmosphere exhibited good photoreduction of chromium (VI).